1990
DOI: 10.1086/208539
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Based Inferences during Consumer Choice

Abstract: This study explores consumers' inference strategies in a mixed choice task involving memory, external information, and missing information on attribute values for some brands. Accessibility of relevant information was manipulated, and both instructed and uninstructed or natural inferences were studied. Instructed inferences by low accessibility subjects conformed more with prior overall evaluations of the brands, displaying evaluative consistency. Instructed inferences by high accessibility subjects tended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
1
12

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(253 citation statements)
references
References 21 publications
(33 reference statements)
5
235
1
12
Order By: Relevance
“…The perception of a colour by people changes depending on the associations related to the colour. According to previous studies, there is a general description of the emotions and associations that different colours evoke (Dick, 1990, Lüscher, 1969.…”
Section: Influence Of Colour On Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of a colour by people changes depending on the associations related to the colour. According to previous studies, there is a general description of the emotions and associations that different colours evoke (Dick, 1990, Lüscher, 1969.…”
Section: Influence Of Colour On Consumer Behaviourmentioning
confidence: 99%
“…For example, in their work Dick (1990) state that the importance of the brand on consumer perception increases during online shopping due to the limited number of other attributes of the product, which the consumer can examine, such as taste, smell, texture or a complete list of ingredients. As a result, the consumer primarily relies on the brand image and reputation.…”
Section: Introductionmentioning
confidence: 99%
“…First, in a process known as evaluative consistency, consumers examine known attributes to infer an overall impression of a product or brand and assume that missing attributes adhere to this impression (Beckwith and Lehmann 1975;Broniarczyk and Alba 1994;Cooper 1981;Dick, Chakravarti, and Biehal 1990;Nisbett and Wilson 1977). Second, in a similar but more complex process, known as probabilistic consistency, consumers examine a known attribute and infer a missing attribute level based on prior beliefs about the correlation between attributes (Downing, Sternberg, and Ross 1985;Ford and Smith 1987;Hoch 1984;Huber and McCann 1982;John, Scott, and Bettman 1986;Kardes and Sanbonmatsu 1993;Meyer 1981;Ross and Creyer 1992).…”
Section: Inferences About Forgotten Product Featuresmentioning
confidence: 99%
“…Substantial past research has found that consumers often prefer a fully described product over an equivalent product from memory (Biehal and Chakravarti 1982, 1983Lynch and Srull 1982) or a product that is only partially described (Kivetz and Simonson 2000). This research has attributed this advantage to consumers choosing the option about which they have greater confidence and less uncertainty (Dick, Chakravarti, and Biehal 1990), consistent with the uncertainty effect (Gneezy, List, and Wu 2006). However, other research has found preferences for products from memory is very context dependent (Alba, Marmorstein, and Chattopadhyay 1992), and consumers tend to choose products with incomplete information when the information that is available is positive (Sanbonmatsu et al 2003).…”
Section: Choices From Memorymentioning
confidence: 99%
See 1 more Smart Citation